Estudio de Factibilidad para la Implementación de una Empresa Productora y Comercializadora de abono orgánico (Bocashi), para el Cantón Loja - Salinas Patiño, Magaly Vanessa (2017)
As is known to all people, serious conditions are currently being suffered as a result of environmental pollution, due to the use of pollutants and noxious substances in soils and crops, which have a harmful effect on health and Well-being of people. Without a doubt all these factors are not of importance for some people, since they only think of obtaining a profitability, no matter to whom they affect. That is why this project has as purpose to carry out a "FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A COMPANY PRODUCER AND COMMERCIALIZER OF ORGANIC FERTILIZER (BOCASHI), FOR THE CANTON LOJA". Same that it will contribute either a minimum percentage to the reduction of environmental pollution, since this is a healthy product and friendly for both the environment and crops and therefore beneficial to the health of people. Also the general objective as the specific objectives were developed and fulfilled in each of the stages of this study. In the market study, surveys and interviews were applied in order to know the supply and demand of the fertilizer, also allowing to know its price and presentation. In addition, this study revealed that there is a future demand for 59,134 bags of fertilizer and An offer of 9,564 sacks, data that obtained an unsatisfied demand of 49,570 bags of 40 kilos of fertilizer for the year 1. Also within the technical study was determined the installed and used capacity that will be 100%, which will allow to produce 840,000 kilograms 6 per year, which is equivalent to 21,000 bags of 40 kilos. The company will be located in the district Tres Leguas km 16 via Malacatos, which was decided after having analyzed several factors. In the organizational study the company will be constituted as Unipersonal, in addition to that it was proposed the organic, functional and positional structure of the new production unit as well as the function manuals. The total investment required by the company "PRONASUR" E.U.R.L, is $ 21,987.20, of which $ 11,987.20 will be contributed by owner manager, equivalent to 54.52%, while the remaining $ 10,000.00 Equivalent to 45.48%, will be financed by BanEcuador bank at an interest rate of 11%. The unit cost of the 40 kg bags for the first year will be $ 5.01 cents, with a profit margin of $ 0.15, leaving the retail price of $ 5.76 each bag, obtaining an income for sales of $ 121. 050.35 dollars for the first year. Within the financial evaluation of the project the following results are observed: the NPV (net present value) of $ 21,448.95; IRR (internal rate of return) of 40.80%; RBC (cost-benefit ratio) of $ 0.15 cents per dollar invested; PRC (period of capital recovery), is in 2 years, 0 months,18 days; And the sensitivity analysis that indicates that the project supports an increase in costs of 6.70%, giving a total of 0.96%, and the sensitivity with decrease of income up to 5.87%, giving a total of 0 , 99, so the project is feasible All these results indicate that it is feasible to launch this project, since all the indicators are positive, more than that an advantage of the 7 project is that the product to offer is new in the market, since there are no companies that dedicate themselves to Produce this type of fertilizer, there are only two entities in Loja that sell a similar product (compost and humus) the Municipality of Loja and the company DEPROSUR of the Prefecture of Loja. Another positive point of the project is that bocashi is one of the most complete and beneficial fertilizers for both the soil and the development of the fields, as well as having the advantage of being obtained in a period of 30 days, while fertilizers Competition is obtained in a period of six months. Finally, we have the conclusions and recommendations, which were made with the results obtained in the development of the project, plus the bibliography that supported the theoretical and referential framework, as well as the annexes that support the project study.